The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5539/ijel.v9n6p148
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Political Discourse Features in English and Arabic

Abstract: This article is devoted to examine political discourse, in particular features of political speeches in English and Arabic Language. Political speeches are often shaped in a specific cultural and social context, using various linguistic features to persuade the public of the speaker’s goals. The study has two aims: firstly, it intends to highlight the prominent features of political discourse in English and Arabic. For example, the use of metaphor and metonymy, pronouns, intertextuality, repetition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Fairclough, 2017). Several researchers have investigated the use of rhetorical strategies in Arabic, including rhetorical questions, repetition, figurative speech, religious phrases and pronouns (Koch, 1983;Johnstone, 1991;Ahluwalia & Burnkrant, 2004;Suchan, 2014;Shakour, 2014;Alduhaim, 2019). This study aims to identify the rhetorical strategies employed in ten Saudi TEDx talks to uncover how language in these talks shapes or is shaped by ideological assumptions and power relations.…”
Section: Persuasive Strategies In Arabic: Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Fairclough, 2017). Several researchers have investigated the use of rhetorical strategies in Arabic, including rhetorical questions, repetition, figurative speech, religious phrases and pronouns (Koch, 1983;Johnstone, 1991;Ahluwalia & Burnkrant, 2004;Suchan, 2014;Shakour, 2014;Alduhaim, 2019). This study aims to identify the rhetorical strategies employed in ten Saudi TEDx talks to uncover how language in these talks shapes or is shaped by ideological assumptions and power relations.…”
Section: Persuasive Strategies In Arabic: Backgroundmentioning
confidence: 99%
“…Another linguistic strategy utilised to sway the audience is the use of religious phrases (Alduhaim, 2019). Speakers may use religious phrases to demonstrate power and authority, or to establish an emotional connection with the audience (Suchan, 2014).…”
Section: Persuasive Strategies In Arabic: Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen in one of the recently published study, the use of the pronoun "they" in post-colonization Arabic political speeches is not the only common feature among them. It is suggested that there are similarities and common features among Arabic political speeches of different Arab countries such as intertextuality, repetition and the use of pronouns (Alduhaim, 2019).…”
Section: A More Recent Eramentioning
confidence: 99%